Optimizing Stope Design in a Deeper Mining Zone at the Musselwhite Mine - Anna P. Perry; Ali Hashemi (Canadian Institute of Mining, Metallurgy and Petroleum, 2023)
The PQ Deeps (PQD) is a production zone located at Newmont’s Musselwhite Mine in northern Ontario. Development started for the PQD in late 2017, and the first stopes were mined starting in early 2021. Unlike most historic longitudinal stoping of narrower orebodies at Musselwhite, the PQD is a wider orebody following the plunge of a fold hinge and is extracted primarily by transverse stoping. Some geotechnical challenges were experienced during early stoping efforts, necessitating design changes throughout late 2021 and early 2022 to optimize the stope design. This work describes the mining methods and design changes to transverse PQD stoping based on geotechnical lessons learned during early stoping efforts.